Comparison of Stone Retrieval Basket, Stone Cone and Holmium Laser: Which One Is Better in Retropulsion and Stone-Free Status for Patients with Upper Ureteral Calculi? - Allameh, Farzad; Razzaghi, Mohammadreza; Fallah karkan, Morteza; Hosseini, Behnam; Tayyebi azar, Ali; Rahavian, Amir Hossein; Ranjbar, Arash; Ghiasy, Saleh (Journal of Lasers in Medical Sciences, 2019)
Introduction: Transurethral lithotripsy (TUL) is an appropriate treatment for ureteral stones and is usually used for stones in the middle and lower part of the ureter. Different devices such as Holmium laser, stone basket and stone cone exist to prevent any fragments from retropulsion during TUL. The present study aims to compare the advantages and disadvantages of the Holmium laser, stone basket and stone cone. Methods: A retrospective study was conducted from September 2016 to January 2018 comparing various TUL methods in 88 subjects with proximal ureteral calculi. The study participants were devided into four matched groups. The first one included 20 patients undergoing TUL with no device (Group 1), the second group included 22 patients undergoing TUL while using the stone retrieval basket, the third group included 18 patients undergoing TUL while utilizing the stone cone and the fourth group included 28 patients undergoing TUL while using Hol-YAG laser. Results: A residual stone ≥ 3 mm was recorded in 15.9% of the patients. stone free rate were seen in 100%, 90.9, 83.3%and 55% in Holmium laser group, retrieval basket group, stone cone group and no device group respectively(p:0.001). Lowest rate of surgery complications including ureteral perforation, Post-operative fever and mucosal damage between 4 groups (p: 0.003) and highest time of surgery (p: 0.001) belong to laser group. If we want to ignore the laser group, success rate for lithotripsy was better in both groups with stone retrieval device compared to the no device group, but no advantage existed between stone basket and stone cone. Conclusion:We can safely conclude that laser significantly help to prevent stone migration during TUL. If we want to ignore the laser group, success rate for lithotripsy was significantly better in both groups with stone retrieval device compared to the no device group, but no advantage existed between stone basket and stone cone.